2018
DOI: 10.1108/ijphm-02-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes toward traditional Chinese medicine and how they affect medical treatment choices in Hong Kong

Abstract: Purpose This study aims to test a conceptual model using public attitudes toward biomedicine and traditional Chinese medicine (TCM) to predict respondents’ medical treatment choice. Design/methodology/approach A quantitative online survey was conducted using quota sampling. Altogether 1,321 questionnaires from Hong Kong residents of age 15 years or above were collected. Findings Attitudes toward biomedicine in relation to TCM and perceived cost of TCM consultation were found to be significant variables in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This finding also validates the importance of attitude as one of the determinants of intention in TPB in which a person is favourable towards and willing to pay for TCAM. This confirms previous findings by Jasamai et al (2017), Chan and Tsang (2018); and Kristoffersen et al (2018) where respondents taking TCAM were found to have more positive attitudes towards TCAM than those not taking TCAM. A study among adults from 32 countries by Peltzer and Pengpid (2016) also found that users were highly satisfied with the use of TCAM.…”
Section: Discussion and Practical Implications Of The Studysupporting
confidence: 92%
See 1 more Smart Citation
“…This finding also validates the importance of attitude as one of the determinants of intention in TPB in which a person is favourable towards and willing to pay for TCAM. This confirms previous findings by Jasamai et al (2017), Chan and Tsang (2018); and Kristoffersen et al (2018) where respondents taking TCAM were found to have more positive attitudes towards TCAM than those not taking TCAM. A study among adults from 32 countries by Peltzer and Pengpid (2016) also found that users were highly satisfied with the use of TCAM.…”
Section: Discussion and Practical Implications Of The Studysupporting
confidence: 92%
“…A study among adults from 32 countries by Peltzer and Pengpid (2016) also found that users were highly satisfied with the use of TCAM. Respondents also had strong beliefs about traditional medicine’s efficacy and role in preventive care (Chan and Tsang, 2018). This implies that users are now more open to using TCAM in treating illness.…”
Section: Discussion and Practical Implications Of The Studymentioning
confidence: 99%
“…Considering the purposes of this study, the nature of the research and the available resources, data was collected from a convenience sample. Like other studies (Ferreira and Barbosa, 2017; Chan and Tsang, 2018), an online questionnaire was created and sent to respondents who received all the information to complete the questionnaire and share it. The use of a snowball method, which has been commonly used to explore the relationship between brands and consumers, has been seen by researchers (Albert et al ,2008; Valta, 2013), as a valid way to collect data.…”
Section: Methodsmentioning
confidence: 99%
“…The public perception of traditional Chinese medicine is strongly affected by the perceived insufficient scientific evidence ( Sun et al, 2017 ). However, older persons are more likely to use Chinese medicine for their illnesses ( Chan & Tsang, 2018 ). The establishment of the Chinese Medicine Development Fund aims to promote the development of the Chinese medicine by enhancing public knowledge and scientific support of Chinese medicine.…”
Section: Affordable Essential Medicines and Vaccines For Allmentioning
confidence: 99%